Creating a historical sport narrative of Zonnebloem College for classroom practice (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article attempts to create a sport narrative of the Zonnebloem College prior to 1950. The introduction provides a motivation for proceeding with a decolonising format and lays out what the elements of such a format would entail. Next, an overview of sport historical developments at the Zonnebloem College is explored. The administrative history of sport at Zonnebloem is explored as well as selected sport codes. Finally, the article is summarised and concluded by presenting teachers and learners with sample questions, which they could consider using in their local conditions.